(untitled) (Bangladesh Journal of Medical Science, 2026)
Background One of the effective methods for reducing mortality and morbidity among preterm newborns is the Kangaroo Mother Care (KMC) method. However, numerous barriers to implementing this method in neonatal units exist. Therefore, alternative methods replacing KMC in the care of preterm newborns are relevant. Objective To determine the effectiveness of using a diaper, which was placed on the mother’s chest for 12-24 hours and then used as a “nest” for the preterm newborn, on neonatal mortality and morbidity rates. Materials and Methods A randomized controlled trial involving preterm infants with extremely and very low birth weight. The control group consisted of preterm infants cared for using the KMC method, and the main group comprised preterm infants in whose care diapers that had been placed on the mother’s chest were used. Results Statistical data analysis revealed no significant differences in outcomes between the alternative approach and KMC, which may have been influenced by the small sample size. The number of fatal outcomes was similar in both groups, although children in the main group required intensive care for longer (11.48 vs. 8.32 days). The incidence of sepsis in post-mortem diagnoses was lower in the main group. The duration of using second- and third-line antibiotics did not differ between the two groups. Conclusion Despite the absence of statistically significant differences between the groups, the obtained data indicate the potential clinical applicability of this approach in settings where the implementation of the KMC method is limited or temporarily impossible. Bangladesh Journal of Medical Science Vol. 25 No. 03 July’26 Page: 848-855